EXERCISE 3A
Question 1:
Factorize:
9x2 + 12xy
Answer 1:
We have:
9x2+12xy=3x(3x+4y)
Question 2:
Factorize:
18x2y − 24xyz
Answer 2:
We have:
18x2y−24xyz=6xy(3y−4z)
Question 3:
Factorize:
27a3b3 − 45a4b2
Answer 3:
We have:
27a3b3−45a4b2=9a3b2(3b−5a)
Question 4:
Factorize:
2a(x + y) − 3b(x + y)
Answer 4:
We have:
2a(x+y)−3b(x+y)=(x+y)(2a−3b)
Question 5:
Factorize:
2x(p2 + q2) + 4y(p2 + q2)
Answer 5:
We have:
2x(p2+q2)+4y(p2+q2)=2[x(p2+q2)+2y(p2+q2)]=2(p2+q2)(x+2y)
Question 6:
Factorize:
x(a − 5) + y(5 − a)
Answer 6:
We have:
x(a−5)+y(5−a)=x(a−5)−y(a−5)
=(a−5)(x−y)
Question 7:
Factorize:
4(a + b) − 6(a + b)2
Answer 7:
We have:
4(a+b)−6(a+b)2=2(a+b)[2−3(a+b)]
=2(a+b)(2−3a−3b)
Question 8:
Factorize:
8(3a − 2b)2 − 10(3a − 2b)
Answer 8:
We have:
8(3a−2b)2−10(3a−2b)=2(3a−2b)[4(3a−2b)−5]
=2(3a−2b)(12a−8b−5)
Question 9:
Factorize:
x(x + y)3 − 3x2y(x + y)
Answer 9:
We have:
x(x+y)3−3x2y(x+y)=x(x+y)[(x+y)2−3xy]
=x(x+y)[x2+y2+2xy−3xy]=x(x+y)(x2+y2−xy)
Question 10:
Factorize:
x3 + 2x2 + 5x + 10
Answer 10:
We have:
x3+2x2+5x+10=(x3+2x2)+(5x+10)
=x2(x+2)+5(x+2)=(x+2)(x2+5)
Question 11:
Factorize:
x2 + xy − 2xz − 2yz
Answer 11:
We have:
x2+xy−2xz−2yz=(x2+xy)−(2xz+2yz) =x(x+y)−2z(x+y) =(x+y)(x−2z)
Question 12:
Factorize:
a3b − a2b + 5ab − 5b
Answer 12:
We have:
a3b−a2b+5ab−5b=b(a3−a2+5a−5) =b[(a3−a2)+(5a−5)]
=b[a2(a−1)+5(a−1)]=b(a−1)(a2+5)
Question 13:
Factorize:
8 − 4a − 2a3 + a4
Answer 13:
We have:
8−4a−2a3+a4= (8−4a)−(2a3−a4) = 4(2−a)− a3(2−a) = (2−a) (4 − a3)
Question 14:
Factorize:
x3 − 2x2y + 3xy2 − 6y3
Answer 14:
We have:
Question 15:
Factorize:
px − 5q + pq − 5x
Answer 15:
We have:
Question 16:
Factorize:
x2 + y − xy − x
Answer 16:
We have:
Question 17:
Factorize:
(3a − 1)2 − 6a + 2
Answer 17:
We have:
Question 18:
Factorize:
(2x − 3)2 − 8x + 12
Answer 18:
We have:
Question 19:
Factorize:
a3 + a − 3a2 − 3
Answer 19:
We have:
Question 20:
Factorize:
3ax − 6ay − 8by + 4bx
Answer 20:
We have:
Question 21:
Factorize:
abx2 + a2x + b2x + ab
Answer 21:
We have:
Question 22:
Factorize:
x3 − x2 + ax + x − a − 1
Answer 22:
We have:
Question 23:
Factorize:
2x + 4y − 8xy − 1
Answer 23:
We have:
2x+4y−8xy−1=(2x−8xy)−(1−4y)
=2x(1−4y)−1(1−4y)=(1−4y)(2x−1)
Question 24:
Factorize:
ab(x2 + y2) − xy(a2 + b2)
Answer 24:
We have:
ab(x2+y2)−xy(a2+b2)=abx2+aby2−a2xy−b2xy
=(abx2−a2xy)−(b2xy−aby2)=ax(bx−ay)−by(bx−ay)=(bx−ay)(ax−by)
Question 25:
Factorize:
a2 + ab(b + 1) + b3
Answer 25:
We have:
a2+ab(b+1)+b3=a2+ab2+ab+b3
=(a2+ab2)+(ab+b3)=a(a+b2)+b(a+b2)=(a+b2)(a+b)
Question 26:
Factorize:
a3 + ab(1 − 2a) − 2b2
Answer 26:
We have:
a3+ab(1−2a)−2b2=a3+ab−2a2b−2b2
=(a3−2a2b)+(ab−2b2)=a2(a−2b)+b(a−2b)=(a−2b)(a2+b)
Question 27:
Factorize:
2a2 + bc − 2ab − ac2
Answer 27:
We have:
2a2+bc−2ab−ac=(2a2−2ab)−(ac−bc)
=2a(a−b)−c(a−b)=(a−b)(2a−c)
Question 28:
Factorize:
(ax + by)2 + (bx − ay)2
Answer 28:
We have:
(ax+by)2+(bx−ay)2=[(ax)2+2×ax×by+(by)2]+[(bx)2−2×bx×ay+(ay)2]
=a2x2+2abxy+b2y2+b2x2−2abxy+a2y2=a2x2+b2y2+b2x2+a2y2=(a2x2+b2x2)+(a2y2+b2y2)=x2(a2+b2)+y2(a2+b2)=(a2+b2)(x2+y2)
Question 29:
Factorize:
a(a + b − c) − bc
Answer 29:
We have:
Question 30:
Factorize:
a(a − 2b − c) + 2bc
Answer 30:
We have:
Question 31:
Factorize:
a2x2 + (ax2 + 1)x + a
Answer 31:
We have:
Question 32:
Factorize:
ab(x2 + 1) + x(a2 + b2)
Answer 32:
We have:
Question 33:
Factorize:
x2 − (a + b)x + ab
Answer 33:
We have:
Question 34:
Factorize:
No comments:
Post a Comment